Law and Morals in Health Services in Indonesia - Br.Sembiring, Tamaulina; Pangaribuan, Donald Rudi (PT FORMOSA CENDEKIA GLOBAL, 2024)
Law is closely related to morality. Law has no meaning if it is not accompanied by morals, so the quality of law is largely determined by moral quality. Law is more codified than morality, written down and more systematically arranged in statutory regulations. The law limits itself to outward behavior, while morals concern a person's inner attitude as a legal subject. Law is based on the will of society and ultimately on the will of the state and morality is based on moral norms that transcend individuals and society. Abandoning morals in law is the same as the law losing its spirit.